Social and individual subjectivity from an historical cultural standpoint - Rey, Fernando Luis González (Outlines. Critical Practice Studies, 2007)
This paper discusses theoretical issues concerning the topic of subjectivity as it has been recently developed within a cultural – historical framework. This provides a new theoretical and epistemological basis to this issue that does not lead to the misinterpretations of subjectivity found in the modern philosophical approaches to theorizing consciousness. This paper builds on interpretations related to Vygotsky’s theory of consciousness that do not follow the current dominant interpretations in Western Psychology. The analyses take departure in the concept of ‘sense’ introduced by Vygotsky at the end of his work and proceeds to propose the concept of subjective sense as the corner stone for the study of subjectivity. The concept of subjective configuration is discussed and finally, the concept of social subjectivity is introduced understood as those symbolic processes and subjective senses that characterize social scenarios and institutions.